Hematological Parameters Among Adult Patients Diagnosed With Type 2 Diabetes Mellitus at Jimma University Medical Center, Jimma, Southwest, Ethiopia - Edosa Tadasa; Eman Kemal (Advances in Hematology)
Conclusion: This study found a prevalence of hematological abnormalities in adults with T2DM, including anemia, elevated WBC count, increased neutrophils, and thrombocytopenia. Anemia was associated with advanced age, while leukocytosis was associated with a longer diabetes duration. Therefore, it is recommended to start regularly screening T2DM patients for hematological abnormalities to improve clinical practice, guide treatment decisions, and develop targeted interventions.